Genetic analysis of the correlation between GLP1 action and metabolic liver disease: Insights from Mendelian randomization analysis - Zhiqiang Ma; Binyu Wang; Danpei Li; Xi Chen (Journal of Diabetes Investigation)
ABSTRACT Purpose Previous studies have shown that glucagon‐like peptide 1 (GLP1) receptor agonists may help improve metabolic dysfunction‐associated steatotic liver disease (MASLD), but supportive genetic data remain limited. Our study aims to explore the correlation between GLP1 action and MASLD. Methods Mendelian randomization (MR) was performed, with 22 cis‐eQTLs and 2 missense mutations used as proxies for GLP1 action. MASLD data from the FinnGen study served as the primary analysis, with replication in an independent cohort. Subsequently, mediation analyses were conducted to explore the role of MASLD risk factors in the correlation between GLP1 action and MASLD. Finally, phenome‐wide association studies (Phe‐WAS) were performed. Results Using cis‐eQTLs as exposure, genetically predicted GLP1 action was associated with a decreased risk of MASLD in the primary analysis [IVW: odds ratio (OR): 0.36; 95% confidence interval (CI): 0.30–0.44; P = 1.37E‐22] and in the replication study (IVW: OR: 0.61; 95% CI: 0.47–0.81; P = 5.58E‐04). In mediation analyses, the proportion of the mediation effect of GLP1 action via type 2 diabetes was 6% (95% CI: 0.0004–0.1138; P = 4.70E‐02), via hypertension was 4% (95% CI: 0.0128–0.0675; P = 3.82E‐03), while via high‐density lipoprotein cholesterol was 1% (95% CI: 0.0039–0.0187; P = 2.52E‐03). Using missense mutations as exposure, no causal relationship between GLP1 action and MASLD was observed. Phe‐WAS showed cardiovascular and renal benefits of GLP1 action. Conclusions Our genetic analysis suggests a possible causal relationship between GLP1 action and MASLD.